Neural basis of the crossmodal correspondence between auditory pitch and visuospatial elevation. (April 2018) - McCormick, Kelly; Lacey, Simon; Stilla, Randall; Nygaard, Lynne C.; Sathian, K.
Abstract: Crossmodal correspondences refer to associations between otherwise unrelated stimulus features in different sensory modalities. For example, high and low auditory pitches are associated with high and low visuospatial elevation, respectively. The neural mechanisms underlying crossmodal correspondences are currently unknown. Here, we used functional magnetic resonance imaging (fMRI) to investigate the neural basis of the pitch-elevation correspondence. Pitch-elevation congruency effects were observed bilaterally in the inferior frontal and insular cortex, the right frontal eye field and right inferior parietal cortex. Independent functional localizers failed to provide strong evidence for any of three proposed mechanisms for crossmodal correspondences: semantic mediation, magnitude estimation, and multisensory integration. Instead, pitch-elevation congruency effects overlapped with areas selective for visually presented non-word strings relative to sentences, and with regions sensitive to audiovisual asynchrony. Taken together with the prior literature, the observed congruency effects are most consistent with mediation by multisensory attention. Highlights: Functional neuroimaging study of pitch-elevation crossmodal correspondence. Minimal evidence for mediation by semantic or multisensory integrative processes. Weak support for involvement of magnitude estimation. Possible relationship to phonological processing. Pitch-elevation congruency likely depends on multisensory attention/working memory.